Nomenclatural conspectus of Paepalanthus ser. Dimeri (Eriocaulaceae) - Picanço, Wellerson; Gonçalves-Esteves, Vania; Trovó, Marcelo (Phytotaxa, 2026)
Paepalanthus (Eriocaulaceae) is a megadiverse Neotropical genus with many nomenclatural and taxonomic problems. Adjustments are therefore required to improve the taxonomy of the genus and clarify species’ morphological boundaries. Based on the literature and analysis of relevant specimens, we present a strictly nomenclatural survey of the 21 names included in Paepalanthus ser. Dimeri considering a detailed historical perspective. We propose four lectotypes, one second-step lectotype, and point out four illegitimate names and one nomen nudum, in addition to providing two type citation corrections.